Loxhd1b inhibits the hair cell development in zebrafish: Possible relation to the BDNF/TrkB/ERK pathway - Liu, Jingwen; Zhang, Xu; Zhang, Qingchen; Wang, Rongrong; Ma, Jingyu; Bai, Xiaohui; Wang, Dawei (Frontiers in Cellular Neuroscience, 2022)
Background Mutations in lipoxygenase homology domain 1 (LOXHD1) cause autosomal recessive inheritance, leading to high-frequency and intermediate-frequency hearing losses in patients. To date, studies on the localization of LOXHD1 gene expression are limited. In this study, we aimed to observe the expressions of Loxhd1b in zebrafish, C57BL/6 murine cochlea, and HEI-OC1 cells. Methods The expression of Loxhd1b in the auditory system of zebrafish was explored by in situ hybridization experiments of zebrafish embryos. The expression of Loxhd1b in cochlear and HEI-OC1 cells of C57BL/6 mice was analyzed by immunofluorescence staining. Confocal microscopic in vivo imaging was used to detect the number and morphological characteristics of lateral line neuromasts and inner ear hair cells in zebrafish that knocked down Loxhd1b gene. The effect of knockdown Loxhd1b gene on the development of zebrafish otolith and semicircular canal was observed using microscopic. Transcriptome sequencing was used to identify downstream molecules and associated signaling pathways and validated by western blotting, immunostaining, and rescue experiments. Results Results of the in situ hybridization with zebrafish embryos at different time points showed that Loxhd1b was expressed in zebrafish at the inner ear and olfactory pores, while the immunostaining showed that Loxhd1 was expressed in both C57BL/6 mouse cochlea and HEI-OC1 cells. Loxhd1b knockdown causes a decrease in the number of spinal and lateral line neuromasts in the inner ear of zebrafish, accompanied by weakened hearing function, and also leads to developmental defects of otoliths and ear follicles. The results of transcriptomics analysis revealed the downstream molecule brain-derived neurotrophic factor (BDNF) and verified that Loxhd1b and BDNF regulate the formation of zebrafish hair cells by synergistic regulation of BDNF/TrkB/ERK pathway based on western blotting, immunostaining, and rescue experiments. Conclusion This was the first time that the BDNF/TrkB/ERK pathway was identified to play a critical role in the molecular regulation of the development of zebrafish hair cells and the auditory development by Loxhd1b.